Application of Macro Role Play to Improve Independence at TK Kemala Bhayangkari 101 Donomulyo Malang - Tria Novika Sari; Ayu Asmah; Siti Muntomimah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Independence relates to a child's ability to recognize their own needs, make decisions, and take responsibility for their actions, including daily activities such as eating independently. Based on initial observations at TK Kemala Bhayangkari 101 Donomulyo, Malang Regency, most Group A children had not shown optimal independence, particularly in eating and drinking activities. This study aims to improve children's independence through the application of the macro role-play method. The research used a collaborative Classroom Action Research (CAR) design conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects were 22 children from Group A. Data collection techniques were carried out through observation and documentation with Independence Learning Objective Achievement Criteria (KKTP) including the ability to take food by themselves, eat and finish food independently, and tidy up eating utensils. The results showed that children's independence at the pre-action stage was 32.56%, increased to 57.95% in Cycle I, and increased significantly to 90.14% in Cycle II. It is concluded that the macro role-play method can improve the independence of Group A children at TK Kemala Bhayangkari 101 Donomulyo, Malang Regency.